Water Immersion Affects Episodic Memory and Postural Control in Healthy Older Adults. Issue 4 (October 2019) - Bressel, Eadric; Louder, Talin J.; Raikes, Adam C.; Alphonsa, Sushma; Kyvelidou, Anastasia
Abstract : Background and Purpose: Previous research has reported that younger adults make fewer cognitive errors on an auditory vigilance task while in chest-deep water compared with on land. The purpose of this study was to extend this previous work to include older adults and to examine the effect of environment (water vs land) on linear and nonlinear measures of postural control under single- and dual-task conditions. Methods: Twenty-one older adult participants (age = 71.6 ± 8.34 years) performed a cognitive (auditory vigilance) and motor (standing balance) task separately and simultaneously on land and in chest-deep water. Listening errors (n = count) from the auditory vigilance test and sample entropy (SampEn), center of pressure area, and velocity for the balance test served as dependent measures. Environment (land vs water) and task (single vs dual) comparisons were made with a Wilcoxon matched-pair test. Results: Listening errors were 111% greater during land than during water environments (single-task = 4.0 ± 3.5 vs 1.9 ± 1.7; P = .03). Conversely, SampEn values were 100% greater during water than during land environments (single-task = 0.04 ± 0.01 vs 0.02 ± 0.01; P < .001). Center of pressure area and velocity followed a similar trend to SampEn with respect to environment differences, and none of the measures were different between single- and dual-task conditions ( P > .05). Conclusions: The findings of this study expand current support for the potential use of partial aquatic immersion as a viable method for challenging both cognitive and motor abilities in older adults.